Alkali‐Metal‐Mediated Magnesiations of an N‐Heterocyclic Carbene: Normal, Abnormal, and "Paranormal" Reactivity in a Single Tritopic Molecule. Issue 47 (29th September 2015) - Martínez‐Martínez, Antonio J.; Fuentes, M. Ángeles; Hernán‐Gómez, Alberto; Hevia, Eva; Kennedy, Alan R.; Mulvey, Robert E.; O'Hara, Charles T.
Abstract: Herein the sodium alkylmagnesium amide [Na4 Mg2 (TMP)6 ( n Bu)2 ] (TMP=2, 2, 6, 6‐tetramethylpiperidide), a template base as its deprotonating action is dictated primarily by its 12 atom ring structure, is studied with the common N‐heterocyclic carbene (NHC) IPr [1, 3‐bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene]. Remarkably, magnesiation of IPr occurs at the para ‐position of an aryl substituent, sodiation occurs at the abnormal C4 position, and a dative bond occurs between normal C2 and sodium, all within a 20 atom ring structure accommodating two IPr 2− . Studies with different K/Mg and Na/Mg bimetallic bases led to two other magnesiated NHC structures containing two or three IPr − monoanions bound to Mg through abnormal C4 sites. Synergistic in that magnesiation can only work through alkali‐metal mediation, these reactions add magnesium to the small cartel of metals capable of directly metalating a NHC. Abstract : Paranormal NHC : When an N‐heterocyclic carbene (NHC) encounters a pre‐inverse‐crown template base, an extraordinary event occurs, thus generating a dative CNa bond at the normal C2‐position, sodiation at the abnormal C4‐position, and magnesiation at the para ‐position of a diisopropylphenyl (Dipp) substituent on N. Structure elucidation and steps towards the target compound are discussed.